Enzyme‐Instructed Assemblies Enable Mitochondria Localization of Histone H2B in Cancer Cells. (31st March 2020) - He, Hongjian; Guo, Jiaqi; Lin, Xinyi; Xu, Bing
Abstract: Presently, little is known of how the inter‐organelle crosstalk impacts cancer cells owing to the lack of approaches that can manipulate inter‐organelle communication in cancer cells. We found that a negatively charged, enzyme cleavable peptide (MitoFlag) enables the trafficking of histone protein H2B, a nuclear protein, to the mitochondria in cancer cells. MitoFlag interacts with the nuclear location sequence of H2B to block it from entering the nucleus. A protease on the mitochondria cleaves the Flag from the MitoFlag/H2B complex to form assemblies that retain H2B on the mitochondria and facilitate H2B entering the mitochondria. Adding NLS, replacing aspartic acid by glutamic acid residues, or changing the l ‐ to d ‐aspartic acid residue on MitoFlag abolishes the trafficking of H2B into mitochondria of HeLa cells. As the first example of the enzyme‐instructed self‐assembly of a synthetic peptide for trafficking endogenous proteins, this work provides insights for understanding and manipulating inter‐organelle communication in cells. Abstract : Cellular pep talk : Carrying a negative charge, the synthetic peptideMitoFlag(l ‐D) forms complexes with the nuclear protein, H2B, and traffics H2B to mitochondria through enzyme‐instructed self‐assembly. This result provides a supramolecular approach for understanding and molecular insights into the inter‐organelle communication.